An Extract from Colored Avocado Seeds Has Anti-Inflammatory Properties - Deepti Dabas; Gregory R. Ziegler; Joshua D. Lambert (Advances in Food Technology and Nutrition Sciences, 2024)
Objective: The anti-inflammatory potential of colored avocado seed extract (CASE) was explored based on the ethnobotanical use of avocado seed for inflammatory diseases. Introduction: Chronic inflammation contributes to many diseases including cancer, cardiovascular diseases, and arthritis. Avocado seeds have been used ethnobotanically for their anti-inflammatory properties. Methods: Lipopolysaccharide (LPS)-stimulated RAW264.7 murine macrophage cells were treated with CASE for 24 h, after which the pro-inflammatory cytokines, Interleukin -6 (IL-6), tumor necrosis factor-α (TNF-α) and IL-1β (Interleukin -1β) were measured along with NO production. Effect of CASE on Cyclooxygenase -2 (COX-2) and prostaglandin E2 (PGE2) was also observed. We also studied if CASE would inhibit the activity of secreted Phospholipase A2 (PLA2). Results: Treatment of LPS-stimulated RAW264.7 cells with CASE for 24 h reduced the production of pro-inflammatory cytokines, IL-6, TNF-α, and IL-1β. NO production was reduced in a dose-dependent manner, and the reduction was associated with a decrease in the protein expression of inducible nitric oxide synthase (iNOS). Whereas PGE2 production was significantly reduced by CASE, no change in the protein expression of Cyclooxygenase -2 (COX-2) was observed. CASE did inhibit the activity of purified secreted PLA2 (IC50=36 μg/mL). Kinetic analysis indicated that the inhibition was non-competitive with respect to substrate concentration. Nuclear translocation of nuclear factor κB (NF-kB) to the nucleus was reduced by treatment with CASE, and this inhibition may underlie the effects of CASE on iNOS and cytokine expression. Conclusion: These results suggest that the CASE may represent a source of anti-inflammatory compounds which can be exploited as functional food ingredients or as lead compounds for pharmaceutical development.